Factors impinging farmers' use of agriculture technology - Abdullah, Farah Adila; Abu Samah, Bahaman (Canadian Center of Science and Education, 2013)
Agriculture is now one of the most important sectors in the Malaysian economy. In order to further develop this sector, technology has become one of the main components. Typically, dealing with the agriculture sector can entail difficulties relating to a number of factors. Consequently, to overcome such problems, farmers are being encouraged to adopt technology that suits their farm. This paper aims to explain technology usage among farmers, and the benefits that can be gained from this technology. Moreover, the paper explains the factors affecting technology usage. Based on the findings, it can be concluded that farmers’ perceptions and levels of education, as well as extension-workers’ knowledge, the management of the extension program, and the physical conditions of the area, are all factors that affect technology adoption among farmers.